الثقافة السياحية ودورها في تنشيط السوق السياحي في الجزائر: ولاية جيجل نموذجا - خروبي, يوسف (جامعة الوادي University of Eloued, 2016)
هدفت هذه الدراسة إلى التعرف على دور الثقافة السياحية في تنشيط السوق السياحي بولاية جيجل وذلك من خلال مسح آراء عينة الدراسة التي اشتملت على 66 فرد (34 سكان محليين، 32 سائح)، حيث تم إخضاع إجابات مفردات الدراسة إلى التحليل عن طريق البرنامج الإحصائي spss. وقد توصلت نتائج الدراسة إلى وجود إدراك للثقافة السياحية من طرف السكان المحليين والسياح، وعدم وجود تأثير للثقافة السياحية لدى سكان المنطقة على السوق السياحي بالولاية ووجود تأثير للثقافة السياحية لدى السياح على السوق السياحي بالولاية. Abstract: The main objective of this study is to understand the role played by tourism culture in boosting the tourism market in the wilaya of Jijel, Algeria. A survey is conducted with a sample of 66 individuals (34 local residents and 32 tourists). The statistical program (SPSS) is used to analyze the answers to the questionnaire. The results show that there is a certain degree of awareness to the tourist culture from both categories (local inhabitants and tourists), but that is only the tourism culture of the tourists wich significantly influences the tourist market in the Region of Jijel.
Political culture and its role in the revitalization of the tourism market
مقال- مجلة رؤى اقتصادية
Keywords: الثقافة السياحية، السوق السياحي، العرض السياحي، الطلب السياحي; the tourism culture, the tourism market, tourist offer, tourist demand